Control Systems Engineering - Nagrath, I. J.; Gopal, M. (New Academic Science, 2021)
The book provides an integrated treatment of continuous and discrete-time systems for two courses at undergraduate level or one course at postgraduate level. The stress is on the interdisciplinary nature of subject and examples have been drawn from various engineering disciplines to illustrate the basic system concepts. A strong emphasis is laid on modeling of practical systems involving hardware; control components of a wide variety are comprehensively covered. Time and frequency domain techniques of analysis and design of control systems have been exhaustively treated and their interrelationship established. Adequate breadth and depth is made available for second course. The coverage includes digital control systems: analysis, stability and classical design; state variables for both continuous and discrete-time systems; observers and pole-placement design; Liapunov stability; optimal control; and recent advances in control systems: adaptive control, fuzzy logic control, neural network control.
Keywords: Automatic control.; elektronické knihy; electronic books